Effect of water-based aerobic training on anthropometric, biochemical, cardiovascular, and explosive strength parameters in young overweight and obese women: a randomized controlled trial - Imen Ben Cheikh; Hamza Marzouki; Okba Selmi; Bilel Cherni; Siwar Bouray; Ezdine Bouhlel; Anissa Bouassida; Beat Knechtle; Yung-Sheng Chen (PeerJ)
Background Obesity is a major health concern that raises the risk of chronic illnesses such as heart disease, diabetes, and metabolic disorders. Traditional workouts such as running or walking can be difficult for overweight individuals due to the heavy impact on joints, which causes discomfort and the possibility of injury. Water-based exercises offer a low-impact alternative that overweight people may find more tolerable. There is minimal research on the specific effects of structured water aerobic exercise on health markers in young overweight and obese women, despite the acknowledged benefits of physical activity for weight control and overall health. This study aimed to assess the effects of 10-week water-based aerobic training (thrice a week) on anthropometric, biochemical, cardiovascular parameters, and explosive strength in young overweight and obese women. Methods In a randomized controlled trial with a pre-to-post testing design, twenty-seven young overweight and obese women (age: 27 ± 1 years; body mass index (BMI) = 30.0 ± 3.1) were randomly assigned into experimental (EG: performing a water-based aerobic training, n = 16) or control (CG: maintaining their usual activities during the intervention, n = 11) groups. The pre- and post-intervention participants were assessed for their anthropometrics (body height, body weight, body mass index (BMI), body fat and circumferences), biochemical (fasting glycemia, total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and triglyceride (TG)), cardiovascular parameters (resting blood pressure and resting heart rate (RHR)), and explosive strength of upper and lower limbs. Results EG showed reductions in body weight, BMI, %BF, fasting glycemia, and TG, along with improvements in HDL-C, LDL-C, RHR, and explosive strength (all p < 0.05; effect size (ES) = 0.180–1.512, trivial to large). In contrast, CG exhibited increases in body weight, BMI, fasting glycemia, LDL-C, and RHR (all p < 0.05; ES = 0.127–0.993, trivial to large), with no significant changes observed in other measured variables. EG showed superior post-test results in fasting glycemia (p < 0.0001; ES = 2.559, large), LDL-C (p < 0.0001; ES = 0.971, large), and explosive strength measures (0.003 ≤ p < 0.0001; ES = 1.145–1.311, large) compared to the CG. Conclusions Our findings indicate that water-based aerobic training could be a useful program to enhance anthropometric, biochemical, cardiovascular, and explosive strength parameters in young overweight and obese women compared to inactive persons.